2012
DOI: 10.1097/bpo.0b013e31825611da
|View full text |Cite
|
Sign up to set email alerts
|

Operative Treatment of Adolescent Clavicle Fractures With an Intramedullary Clavicle Pin

Abstract: Therapeutic level IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(43 citation statements)
references
References 20 publications
0
42
1
Order By: Relevance
“…Previous studies reported the early complications such as nail breakage, bending and threatened skin perforation in the ESIN group [12,22,25]. However, these early complications were not significant in our study, possibly because of routine immobilization in an arm sling for first 1 to 2 weeks and good patient compliance.…”
Section: Vas = Visual Analogue Scalecontrasting
confidence: 70%
See 1 more Smart Citation
“…Previous studies reported the early complications such as nail breakage, bending and threatened skin perforation in the ESIN group [12,22,25]. However, these early complications were not significant in our study, possibly because of routine immobilization in an arm sling for first 1 to 2 weeks and good patient compliance.…”
Section: Vas = Visual Analogue Scalecontrasting
confidence: 70%
“…Traditionally, operative treatment has been achieved by plate and screws [7,10,11]. Recently, intramedullary fixation is gaining increased interest in the literature [12,13]. To the author's knowledge, there is no head-to-head comparison between the elastic stable intramedullary nail (ESIN) and the plate fixation for displaced midshaft clavicle fractures in adolescents.…”
Section: Introductionmentioning
confidence: 99%
“…It seems that the Robinson classification, which was developed for adult fractures, is less suitable for childhood fractures. Recently, Frye et al 15 reported the results of 17 patients treated operatively with an intramedullary pin. The arbeitsgemeinschaft fu¨r osteosynthesefragen pediatric comprehensive classification of long bone fractures does not include the clavicle.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5][6][7][8] Although highquality clinical studies have been completed in the adult population, there is limited data regarding the results of nonoperatively managed clavicle fractures in adolescents, for whom clavicle fractures account for approximately 15% of all fractures. 3,4,[9][10][11][12][13][14][15] Owing to the excellent healing potential in children, even significantly displaced adolescent clavicle fractures have traditionally been treated nonoperatively (Fig. 1).…”
mentioning
confidence: 99%